Investigation on California Bearing Ratio (CBR) characteristics of cement bound shredded tire geocomposite / Chow Shiao Huey and Sayani Khorim - Chow, Shiao Huey; Khorim, Sayani (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2007)
This study investigates the California Bearing Ratio (CBR) characteristics of cement bound shredded tire geocomposite. A total of five test series were conducted to investigate the effect of curing day, repeatability of test specimen, effect of curing condition, effect of cement content and effect of rice husk ash (RHA) as cement replacement material on the cement bound shredded tire geocomposite. The CBR test results revealed that higher curing day and cement content increase the CBR of shredded tire geocomposite. On the contrary, a higher RHA content reduces the CBR of the geocomposite.